Growth Characteristics of some Indigenous Fuelwood and Fodder Tree Species of Sub-tropical Garhwal Himalayas - Mishra, Ashutosh; Nautiyal, S.; Nautiyal, D. P. (Indian Forester, 2009)
Comparative study of normal and quality planting stock of selected indigenous fuelwood and fodder tree species of sub-tropical region of Garhwal Himalaya was carried out for selection of suitable fuelwood and fodder tree species for higher biomass production. Based on the findings of the seed and growth characteristics, it is concluded that Grewia optiva, Bauhinia variegata and Albi ia lebbeck are the best suited tree species for plantations in the sub-tropical region of Garhwal Himalayas.